Direct Determination of Single Nucleotide Polymorphism Haplotype of NFKBIL1 Promoter Polymorphism by DNA Conformation Analysis and Its Application to Association Study of Chronic Inflammatory Diseases - Shibata, Hiroki; Yasunami, Michio; Obuchi, Nobuhisa; Takahashi, Megumi; Kobayashi, Yasushi; Numano, Fujio; Kimura, Akinori (Human Immunology, 2006)
We previously revealed that one of the human leukocyte antigen-linked susceptibility genes for Takayasu’s arteritis (TA) was mapped between TNFA and MICB loci and that −63T allele of NFKBIL1, which is between TNFA and MICB loci, was associated with rheumatoid arthritis (RA) in the Japanese population. We have developed a novel typing method based on reference strand-mediated conformation analysis for the upstream sequence of the NFKBIL1 gene, where −422 (T) 8/(T) 9, −325 C/G, −263 A/G, and −63 T/A polymorphisms were found. Upon the analysis of the patients with TA ( n = 84), those with RA ( n = 120), and healthy control subjects ( n = 217), five common haplotypes named IKBLp*01 through IKBLp*05 were found in the Japanese population. The frequency of IKBLp*03 was significantly increased in the patient with TA (57.1% vs 35.0%, giving an odds ratio of 2.47). In addition, the frequency of IKBLp*01, but not that of other −63T-bearing alleles, was increased in the patients with RA (73.3% vs 58.1%, giving an odds ratio of 1.99), suggesting that the susceptibility to RA was conferred not by −63T alone but by combination of single nucleotide polymorphisms in the NFKBIL1 promoter. A higher promoter activity associated with IKBLp*03 and a lower activity associated with IKBLp*01 may contribute to the susceptibility to TA and RA, respectively.